Dealing with Skin and Blood-Brain Barriers: The Unconventional Challenges of Mesoporous Silica Nanoparticles - Alessandra Nigro; Michele Pellegrino; Marianna Greco; Alessandra Comandè; Diego Sisci; Luigi Pasqua; Antonella Leggio; Catia Morelli (MDPI AG, 2018)
Advances in nanotechnology for drug delivery are fostering significant progress in medicine and diagnostics. The multidisciplinary nature of the nanotechnology field encouraged the development of innovative strategies and materials to treat a wide range of diseases in a highly specific way, which allows reducing the drug dosage and, consequently, improving the patient’s compliance. Due to their good biocompatibility, easy synthesis, and high versatility, inorganic frameworks represent a valid tool to achieve this aim. In this context, Mesoporous Silica Nanoparticles (MSNs) are emerging in the biomedical field. For their ordered porosity and high functionalizable surface, achievable with an inexpensive synthesis process and being non-hazardous to biological tissues, MSNs offer ideal solutions to host, protect, and transport drugs to specific target sites. Extensive literature exists on the use of MSNs as targeted vehicles for systemic (chemo) therapy and for imaging/diagnostic purposes. However, the aim of this review is to give an overview of the last updates on the potential applications of the MSNs for Topical Drug Delivery (TDD) and as drug delivery systems into the brain, discussing their performances and advantages in dealing with these intriguing biological barriers.